THE POTENTIAL OF THE ELDERLY IN THE DEVELOPMENT OF TOURIST ATTRACTIONS IN BO-SUPHAN COMMUNITY SONG-PHI-NONG DISTRICT SUPHANBURI PROVINCE - Amphanthong, Pimpan; Kongpoung, Pittayut; Kamnuanthong, Sunanthra (Journal of Social Science and Cultural, 2023)
This study, the objectives were to 1) study the context of Bo-Suphan community, Song-Phi Nong district, Suphanburi province. That can be developed and upgraded to be a local tourist attraction and 2) the potential of the elderly in developing tourist attractions in the Bo-Suphan community, Song-Phi-Nong district, Suphanburi province. The quantitative sampling is the population quantity that selects representatives of potential elderly, who are ready to jointly develop tourism areas in 4 communities out of 18 communities. It was found that there were 681 people and 50 people were randomly sampled in the area, divided according to the proportion of the population in the area. It was found that from the context of Bo-Suphan community. That has outstanding characteristics of the community, it was used to determine the Bo-Suphan community tourism route, as follows: Point 1 Ban-Nong-Ling weaving community and Mon community. Point 2 Wat-Thap-Kradan community and the legend of the Queen Luk-Thung-Phum-Puang-Duang-Chan song story, Point 3 Organic agricultural products community and Point 4 community on the route of King Rama VI's royal visit. However, the guidelines that want to develop the potential of the elderly to support tourist attractions in the community. Encouraging the elderly to create jobs distribution of income from tourist attractions management readiness, public relations for tourism in the community as a morning-evening return trip in terms of facilities, including travel accommodation and restaurants Including various activities arising from the context of the community reflecting the identity according to the way of life and creative works that are unique and distinctive in the community to enjoy knowledge and basic wisdom local culture on the basis of responsibility Awareness of the preservation of cultural heritage and environmental values by the local community contributes to tourism management.